1980
DOI: 10.1128/aem.39.5.971-975.1980
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 4-hydroxyochratoxin A from ochratoxin A by rat liver microsomes

Abstract: Hydroxyochratoxin A was isolated and identified from the urine of rats after injection with ochratoxin A. By incubating ochratoxin A with rat liver microsomes and reduced nicotinamide adenine dinucleotide phosphate, one major (90%) and two minor metabolites, more polar than ochratoxin A, were formed. Thin-layer chromatography revealed that the major metabolite had Rf values identical to those of hydroxyochratoxin A in six different solvent systems. Formation of the metabolites in vitro was inhibited by carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…The metabolism of OTA has been extensively studied by the team of Størmer during the past 25 years [291] using in vitro and in vivo assays in liver of different animals [292][293][294][295]. The major metabolites are shown in Fig.…”
Section: Metabolism Of Otamentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of OTA has been extensively studied by the team of Størmer during the past 25 years [291] using in vitro and in vivo assays in liver of different animals [292][293][294][295]. The major metabolites are shown in Fig.…”
Section: Metabolism Of Otamentioning
confidence: 99%
“…Formation of the OH-OTA derivatives is modulated by inducers or inhibitors of CYP450, and prostaglandin synthase, which has similar activity to COX and LOX. Indeed, pretreatment of animal with phenobarbital (PB) increased 4(R)-OH-OTA production in hepatocytes [308], rat liver [292,319], rabbit kidney, and in BEAS-2B cells [305]. We have also observed these hydroxylated metabolites in kidney of pig fed OTA [301] and have noted that inhibition of the LOX pathway increases formation of 10-OH-OTA [306].…”
Section: Metabolism Of Otamentioning
confidence: 99%
“…Toxins 2020, 12, 121 3 of 37 (4R)-4-Hydroxyochratoxin A (24), or 4-hydroxyochratoxin A, was isolated from the urine of rats after injection with OTA (21), which indicated that OTA (21) was converted to (4R)-4-hydroxyochratoxin A (24) ( Figure S8) [29].…”
Section: Hydroxylationmentioning
confidence: 99%
“…7-Carboxy-(2 -hydroxy-1phenylalanine-amide)-5-chloro-8-hydroxy-3,4-dihydro-3Rmethylisocoumarin (22) Phenylobacterium immobile (bacterium) [28] Dihydrodiol derivative of ochratoxin A (23) Phenylobacterium immobile (bacterium) [28] (4R)-4-Hydroxyochratoxin A (24) Rat liver microsomes [29] Cell cultures of wheat and maize [29] Rabbit liver microsomes [30] (4S)-4-Hydroxyochratoxin A (25) Cell cultures of wheat and maize [31] Rabbit liver microsomes [30] 10-Hydroxyochratoxin A (26) Rabbit liver microsomes [30] Ochratoxin B (OTB, 27) Hydroquinone metabolite of ochratoxin (OTHQ, 28) Horse radish peroxidase (HPR) [32] Sterigmatocystin (29) 9-Hydroxy sterigmatocystin (30) Human and rat hepatic microsomes [34] T-2 toxin (31) 19-OH T-2 toxin = 3'-OH T-2 toxin (32) Chicken CYP3A37 (enzyme) [35] Zearalenone (ZEN, 33) (5S)-5-Hydroxy ZEN (34) Cunninghamella bainieri (fungus) [38] 13-Hydroxy ZEN (35) Human liver microsomes [40] 15-Hydroxy ZEN (36) Human liver microsomes [40] Toxins 2020, 12, x FOR PEER REVIEW 4 of 37 hydroxy-3,4-dihydro-3Rmethylisocoumarin (22) Dihydrodiol derivative of ochratoxin A (23) Phenylobacterium immobile (bacterium) [28] (4R)-4-Hydroxyochratoxin A (24) Rat liver microsomes [29] Cell cultures of wheat and maize [29] Rabbit liver microsomes [30] (4S)-4-Hydroxyochratoxin A (25) Cell cultures of wheat and maize [31] Rabbit liver microsomes [30] 10-Hydroxyochratoxin A (26) Rabbit liver microsomes [30] Ochratoxin B (OTB,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation